2008
DOI: 10.1007/bf03342703
|View full text |Cite
|
Sign up to set email alerts
|

They’re Natural and Everywhere: How Evaluative Practices Permeate the Organization

Abstract: How do evaluative practices become natural and ubiquitous in an organization? In this paper we integrate findings from previous empirical work on the adoption of evaluative practices in organizations with insights from institutional theory and social psychology research for advancing the understanding of possible states of evaluative practices within organizations and the processes through which organizations become permeated by evaluative practices. Our conceptual model suggests that once evaluative practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…Tensions manifest in conflicts of proponents and opponents who struggle over the appropriate logic (Townley, 1997). In this reasoning, tensions disappear over time as appraisal system opponents lose influence and new performance measures become 'natural' in the organisation (Maier & Brandl, 2008).…”
Section: Theoretical Perspectives For Studying Tensions In Performancmentioning
confidence: 99%
See 1 more Smart Citation
“…Tensions manifest in conflicts of proponents and opponents who struggle over the appropriate logic (Townley, 1997). In this reasoning, tensions disappear over time as appraisal system opponents lose influence and new performance measures become 'natural' in the organisation (Maier & Brandl, 2008).…”
Section: Theoretical Perspectives For Studying Tensions In Performancmentioning
confidence: 99%
“…By displaying how a convention for appraisals incorporates both the accountability and the professional logic, we point out that performance appraisals do not 'have' a specific rationality, as prior research on the adoption of such systems suggested (e.g. Townley, 1997Townley, , 1999Maier & Brandl, 2008). Instead, the logic(s) for interpreting appraisal systems depend on the convention in place.…”
Section: Introductionmentioning
confidence: 95%
“…Die neoinstitutionalistische Forschung geht davon aus, dass Accounts zur Nützlichkeit von Praktiken abgegeben werden, wenn nicht genügend Klarheit über Zweck der Praktik vorhanden ist. Mit wachsender Selbstverständlichkeit des Zwecks einer Praktik geht der Bedarf an der Abgabe von Erklärungen zur Funktion von Praktiken zurück (Maier/Brandl 2008). Dann reicht die Nennung der Praktik aus.…”
Section: Theoretische Orientierungunclassified